2018
DOI: 10.1007/s10508-018-1247-y
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Victimization in a Community Sample of Bisexual and Lesbian Women: An Intersectional Approach

Abstract: Mental health inequities among bisexual and lesbian women are well-documented. Compared to heterosexual women, both bisexual and lesbian women are more likely to report lifetime depressive disorders, with bisexual women often faring the worst on mental health outcomes. Risk factors for depression, such as victimization in childhood and adulthood, are also more prevalent among bisexual women. Less is known about the intersection of racial/ethnic and sexual minority identities, and how depression and victimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…The results showed that sexual minority status was associated with increased risk for psychological distress for both Black adults and White adults. However, the results did not indicate that Black sexual minority adults had significantly higher levels of psychological distress than White sexual minority adults, which is a similar finding in recent studies (Bostwick et al 2018;Velez et al 2017).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The results showed that sexual minority status was associated with increased risk for psychological distress for both Black adults and White adults. However, the results did not indicate that Black sexual minority adults had significantly higher levels of psychological distress than White sexual minority adults, which is a similar finding in recent studies (Bostwick et al 2018;Velez et al 2017).…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, the intersectionality framework was not supported with the finding of a racial non-difference in psychological distress among sexual minority adults. The intersectionality framework has been supported by recent studies on REM sexual minorities that have identified unique stressors that affect Black sexual minority adults such as discrimination experiences and social rejection (Bhambhani et al 2018;Bostwick et al 2018;Calabrese et al 2015). The identified stressors in studies on REM sexual minorities can inform mental health practitioners of evidence-based risk factors that affect Black sexual minority adults.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…29 The higher rates of lifetime depression and trauma reported by SMW of color are consistent with a recent analysis of CHLEW data. 46 No racial/ethnic differences in health behaviors were identified. With a few exceptions, 55 there is a paucity of research examining racial/ ethnic differences in psychosocial and behavioral risk factors for CVD in SMW.…”
Section: Discussionmentioning
confidence: 99%
“…43 Therefore, we assessed lifetime trauma by combining reports of childhood and adulthood trauma based on established methods. [44][45][46] Childhood trauma included physical abuse, sexual abuse, and parental neglect before the age of 18. Childhood physical abuse was assessed with the following item: ''Do you feel that you were physically abused by your parents or other family members when you were growing up?''…”
Section: Methodsmentioning
confidence: 99%